Communication factors in implementing the policy of vocational high school revitalization in South Sumatera province: - - Lestari, Delfiazi Puji; Dwimawanti, Ida Hayu; Larasati, Endang; Purnaweni, Hartuti (Management and Entrepreneurship: Trends of Development, 2022)
This study aims to reveal the communication factors in the implementation of the Vocational Revitalization Policy (Presidential Decree No. 9 of 2016). The research location included SMKN 1 Gelumbang and SMKN 6 Palembang in South Sumatra province. The data were collected through interviews, observation and documentation. The data analyses were carried out by condensing the data, presenting it and drawing conclusions. The results show that first, although the transmission of policy information was carried out in all the revitalization areas through socialization and technical guidance, the distortions were still found. Second, the Industry, Business World, and Work World (IDUKA) did not get the maximum clarity of information on this policy. Third, the submission and clarity of information as well as coordination with the parties related lacked consistency. In the future, schools must be able to create an effective communication with all the elements of implementers and policy target groups so that the policy objectives could be achieved. Jel classification : A21, I280